Operation Control and Analysis of Hybrid Multiterminal HVDC System Using Different Control Strategies under Abnormal Conditions - Syed Tahir Shah (00000206189); Dr Abraiz Khattak (USPCAS-E, NUST, Islamabad, 2021)
TH-244
Keywords: MS-EEP Thesis MS Thesis